Microscopic Insight Of Molecularly Imprinted Sol-Gel Matrix For Creatinine-Recognised Biosensor - Ang, Qian Yee (2018)
Molecularly imprinted polymer (MIP) is important in biomimetic recognition systems owing to its selective molecular recognition towards any guest of interest. Considering the exceptional thermal, chemical and mechanical tolerance under a wide variety of conditions, MIP has been one of the potential “smart” devices in biomedical applications, such as pharmaceutical industry, clinical analysis and in vivo or in vitro sensing. However, one of the major issues that challenges MIP lies on the conformational adaptability of MIP. As compared to the conventional biomedical diagnostics, such as enzyme-linked immunosorbent assay (ELISA), the difficulties in controlling the shape-specificity or molecular memory within MIP for the best molecular fitting has restricted the potential of MIP as a sensing tool. In fact, the optimal morphological integrity is the key factor to define the successful sensing activity by MIP. As such, the present study intends to furnish the key concepts of molecular imprinting, particularly the underlying mechanisms of MIP beyond the usual description of molecular recognition. First, the host-guest chemistry is studied in detail, in terms of intermolecular interactions, to elucidate the recognition behaviour of target molecule (template), creatinine (Cre) by MIP. Cre is a spontaneous and non-enzymatic degradation end product of creatine (Cr) or phosphocreatine metabolism in vertebrates, which serves as a reliable biomarker in assessing renal, thyroid and muscular dysfunction. In this study, the imprinting of Cre is ascertained via sharing of lone pair electrons from nitrogen (N) atom of Cre and oxygen (O) atoms of the sol-gel matrix, respectively, to the Al3+ Lewis acid. To further fortify the shape memory stiffness of MIP, Cre is removed from the organised architecture by a series of eluents via physical means, leaving behind a binding framework with varying steric and functional complementarity to Cre. Referring to the experimental data, the best Cre-molecular memory is imparted by methanol eluent, making MIP capable of selective uptake of Cre up to 19.48 ± 0.64 mg g−1 MIP even in the presence of functionally alike, i.e., Cr, and/or structurally alike interfering analogues, i.e., N-hydroxysuccinimide (N-hyd) and 2-pyrrolidinone (2-pyr), by competitive selectivity coefficients of 3.01 ± 1.11, 3.75 ± 0.57 and 5.24 ± 4.59, respectively. Coupled with the powerful and reliable prediction of chemical properties for biomolecular system, the MIP system is rationalised with the aid of a computational chemistry tool, HyperChem based on the Parameterised Model number 3 (PM3) semi-empirical quantum mechanics method. The molecular modelling has come up with a good agreement between the theoretical computations and the empirical data, which extends the validity of computational screening in the MIP system in an experimental-free approach. Finally, the MIP is film-coated on carbon electrode as an integrated biosensor that translates the chemical response from Cre into an electroanalytical response, reaching ca. 1.4 µA. During artificial urinary sampling, the Cre-MIP film electrode outperforms in the binary mixture analysis, attaining an empirical binary I at 1.4823 ±0.0267 µA for Cre:Cr at 80:20 molar ratio. It is noteworthy that molecular imprinting has once again proven its feasibility in Cre-MIP biosensor through the electrochemical sensing performance. Henceforth, this study has come up with a practical design of MIP for the detection of renal dysfunction by point-of-care testing for Cre.